Structural but Not Functional Alterations in Cones in the Absence of the Retinal Disease Protein Retinitis Pigmentosa 2 (RP2) in a Cone-Only Retina - Li, Linjing; Rao, Kollu N.; Khanna, Hemant (Frontiers in Genetics, 2019)
X-linked retinitis pigmentosa 2 (XLRP2) patients and Rp2null mice exhibit severe cone photoreceptor degeneration. However, due to the paucity of cones in mammalian model systems, it is not clear how cones respond to the loss of RP2. Here we have used the Nrl-/- mice, which develop a rodless and short wavelength (S) opsin-containing cone-only retina, to generate Rp2null::Nrl-/- double knock out (Rp2-DKO) mice. We found that the ciliary axoneme and the outer segments of the cones were significantly longer with disorganized membrane infoldings as compared to the Nrl-/- mice. Additionally, we found misregulation in the expression of the genes related to ophthalmic disease, cell trafficking, and stress-response in the Rp2-DKO mice prior to the onset of cone degeneration. Surprisingly, the loss of RP2 did not affect progressive photoreceptor dysfunction of the Nrl-/- mice and the trafficking of S opsin. Our data suggest that RP2 is a negative regulator of cone outer segment length but does not affect S-opsin trafficking and S-cone function. Our studies also provide a cone-only platform to design cone-targeted therapeutic strategies for X-linked RP2.